A systems approach to risk management through leading safety indicators - Leveson, Nancy (Reliability engineering & system safety, 2015)
The goal of leading indicators for safety is to identify the potential for an accident before it occurs. Past efforts have focused on identifying general leading indicators, such as maintenance backlog, that apply widely in an industry or even across industries. Other recommendations produce more system-specific leading indicators, but start from system hazard analysis and thus are limited by the causes considered by the traditional hazard analysis techniques. Most rely on quantitative metrics, often based on probabilistic risk assessments. This paper describes a new and different approach to identifying system-specific leading indicators and provides guidance in designing a risk management structure to generate, monitor and use the results. The approach is based on the STAMP (System-Theoretic Accident Model and Processes) model of accident causation and tools that have been designed to build on that model. STAMP extends current accident causality to include more complex causes than simply component failures and chains of failure events or deviations from operational expectations. It incorporates basic principles of systems thinking and is based on systems theory rather than traditional reliability theory. •Much effort has gone into developing leading indicators with only limited success.•A systems-theoretic, assumption-based approach may be more successful.•Leading indicators are warning signals of an assumption’s changing vulnerability.•Heuristic biases can be controlled by using plausibility rather than likelihood.